FGD-6: Updating Kurikulum Internasional Bidang Kimia - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
Professor Dr. Ab Malik Marwan Ali and Professor Dr. Norizan Ahmat were "FGD-6: Updating appointed as speakers in a virtual event Internasional Bidang Kimia" November 2020. organised by Fakultas Matematika dan Pengetahuan Alam (FMIPA), Ilmu Universitas Sumatera Utara (USU), Indonesia.